An Opportunity for Charity? A Catholic Tradition in Understanding Disability and Its Impact on Ministry - Masters, Anne ca. 20./21. Jh. (Journal of disability & religion, 2016)
David Perry, the father of a boy with Down Syndrome, wrote an angry reaction to Pope Francis' references to individuals and families living with disabilities in Amoris Laetitia. Perry is con-cerned about the limited perspective of persons with disabilities that is portrayed in the texts, which show families commended for their love and tolerance, with a lack of appreciation for the person with a disability as a person of interest, rather than an object of pity. He offers further reflections of caution and hope in response to words and actions of Pope Francis during a Mass celebrating disability awareness. Perry's comments provide the starting point for reflecting on the image of persons with disabilities presented in Amoris Laetitia and a discussion of possibilities for charity to serve as a corrective for this and pastoral practice.